MOLECULAR COMPOSITION OF COAL LIQUID OIL CHARACTERIZED BY GAS CHROMATOGRAPHY WITH ATOMIC EMMISION DETECTOR - Yusnitati, Yusnitati; Murti, Sri Djangkung Sumbogo (Jurnal Energi dan Lingkungan (Enerlink), 2010)
Heteroatom-containing species in the coal liquid oils (CLO) were identified andquantified by the aid of gas chromatography with atomic emission detector (GCAED).Four different CLOs from different rank coals, processes and cut pointswere investigated in the present study. Thiophene and its derivatives werefound to be the major sulfur compounds, pyridines and anilines, and phenolswere the major nitrogen and oxygen compounds, respectively in the oils ofboiling range 300 ?. An oil of boiling range (300 ? 420?) carried moredimethyldibenzothiophenes and benzoquinolines. The correlation between feedcoal and liquid product was discussed in terms of the compositions ofheteroatomic compounds.Kata kunci: coal liquid oil, heteroatomic compounds, GC-AED